Genetic basis of carbapenem-resistant clinical Serratia marcescens in Japan - Hazim O. Khalifa; Shizuo Kayama; Mohammed Elbediwi; Liansheng Yu; Wataru Hayashi; Yo Sugawara; Mohamed-Yousif Ibrahim Mohamed; Hazem Ramadan; Ihab Habib; Tetsuya Matsumoto; Motoyuki Sugai (Journal of Global Antimicrobial Resistance)
Objective: To investigate the genetic basis of carbapenem resistance in clinical Serratia marcescens isolates collected from patients in Japan between 1994 and 2016. A total of 5135 clinical isolates of S. marcescens were recovered from different medical centres across Japan, identified in central laboratories, and tested for antimicrobial agents using the broth microdilution method. Methods: All the isolates that showed intermediate or resistant phenotypes for at least one carbapenem antibiotic were confirmed by antimicrobial susceptibility testing and for carbapenemase production by the modified carbapenem inactivation method. Furthermore, full genetic characterization was performed by whole genome sequencing for all the isolates. Results: Based on our findings, 27 isolates (0.53%) exhibited resistance to ertapenem and/or meropenem. Among these, 10 isolates were phenotypically confirmed as carbapenemase producers using the modified carbapenem inactivation method test. The isolates were resistant to a wide range of antibiotics including β-lactams (48.1%–100%), two fluoroquinolones (77.8%–88.9%), tigecycline and minocycline (70.4% each), and sulfamethoxazole-trimethoprim (55.6%). Whole-genome sequencing was conducted on all carbapenem-resistant strains, uncovering blaIMP in eight isolates, comprising seven with blaIMP-1 and one with blaIMP-11, alongside multiple antimicrobial resistance determinants. Importantly, the phylogenomic comparison with international S. marcescens isolates revealed genetic relatedness and potential cross-border transmission events. Conclusions: Our findings underscore the importance of enhanced surveillance and infection control measures to mitigate the dissemination of multidrug-resistant pathogens, emphasizing the need for international collaboration and coordinated efforts to address antimicrobial resistance on a global scale.